Brideshead Revisited through the Years: Between Religion and Relationships from Novel to Screen - Verhoef, Anne (Student Undergraduate Research E-journal!, 2016)
Evelyn Waugh’s Brideshead Revisited (1945) has been adapted on-screen twice: as a series in 1981 and as a film in 2008. Even though all three versions present the audience with the same fabula, Charles’s (sexual) orientation has been approached differently throughout the years. Whereas Waugh’s 1945 novel leaves the issue of sexuality unaddressed and focuses on Charles’s conversion to Christianity instead, the 1981 series portrays a homosexual tension between Charles and Sebastian, and the 2008 film foregrounds the heterosexual, or even heteronormative relationship between Charles and Julia. Hence, this paper shows that sexuality functions as a social construction that changes over time, and in doing so offers a corrective view regarding the prevailing image that society has become more sexually tolerant over the years.